2007
DOI: 10.1007/s00395-007-0650-7
|View full text |Cite
|
Sign up to set email alerts
|

Inactivity of nitric oxide synthase gene in the atherosclerotic human carotid artery

Abstract: eNOS transduction in atherosclerotic human carotid artery results in high expression without any measurable activity of the recombinant protein. The defect in the atherosclerotic vessels is neither caused by cofactor deficiency nor enhanced NO breakdown. Since angioplasty is performed in atherosclerotic arteries,eNOS gene therapy is unlikely to provide clinical benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Endothelial dysfunction appears to occur early after reperfusion, signaled by the endothelial generation of a large burst of superoxide radicals [8, 11, 20, 28, 29, 31, 36]. The decrease in endothelium-dependent dilation has been shown to occur soon after the generation of O 2 ·− by the reperfused coronary endothelium [20, 31] suggesting that endothelial generation of O 2 ·− radicals acts as a trigger mechanism for endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction appears to occur early after reperfusion, signaled by the endothelial generation of a large burst of superoxide radicals [8, 11, 20, 28, 29, 31, 36]. The decrease in endothelium-dependent dilation has been shown to occur soon after the generation of O 2 ·− by the reperfused coronary endothelium [20, 31] suggesting that endothelial generation of O 2 ·− radicals acts as a trigger mechanism for endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other studies also reported that release of TNF- α during stent implantation also contributes to impaired dilator response in coronary microcirculation [12]. Many other factors, such as endothelial progenitor cells [38], substances released from surrounding myocardium [53], alteration of NOS gene [139], and endothelial growth factor [62], have also been reported to regulate coronary vasomotor tone.…”
Section: Other Determinants Of Human Coronary Vasomotor Tonementioning
confidence: 99%
“…Correspondingly, eNOS gene transfer is considered an attractive therapeutic option to improve endothelial function. However, although the exogenous expression of eNOS successfully prevented smooth muscle cell migration in vitro (Largiadèr et al, 2008), a similar approach in human atherosclerotic lesions failed because the heterologously expressed eNOS was inactive (Tanner et al, 2007). eNOS.…”
Section: Chronic Treatment With Ang II Stimulates the Phosphorylationmentioning
confidence: 99%